2014
DOI: 10.1371/journal.pone.0100330
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Increase lws Opsin Expression and Red Sensitivity in Male Three-Spined Sticklebacks

Abstract: Optomotor studies have shown that three-spined sticklebacks (Gasterosteus aculeatus) are more sensitive to red during summer than winter, which may be related to the need to detect the red breeding colour of males. This study aimed to determine whether this change of red light sensitivity is specifically related to reproductive physiology. The mRNA levels of opsin genes were examined in the retinae of sexually mature and immature fish, as well as in sham-operated males, castrated control males, or castrated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Matsumoto et al (2014) suggested that speciation by sensory drive most likely occurs when the sensory trait is determined by a small number of loci. Indeed, the visual spectral sensitivity is related to the opsin genes, e.g., long-wavelength-sensitive opsin gene (lws) in cichlids, zebrafish (Danio rerio), and three-spined stickleback (Seehausen et al 2008;Shao et al 2014), or shortwavelength-sensitive opsin gene 2a (sws2a) in cichlids (Seehausen et al 2008). Moreover, body coloration is also likely to be determined by a limited number of genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matsumoto et al (2014) suggested that speciation by sensory drive most likely occurs when the sensory trait is determined by a small number of loci. Indeed, the visual spectral sensitivity is related to the opsin genes, e.g., long-wavelength-sensitive opsin gene (lws) in cichlids, zebrafish (Danio rerio), and three-spined stickleback (Seehausen et al 2008;Shao et al 2014), or shortwavelength-sensitive opsin gene 2a (sws2a) in cichlids (Seehausen et al 2008). Moreover, body coloration is also likely to be determined by a limited number of genes.…”
Section: Discussionmentioning
confidence: 99%
“…Electroretinogram (ERG) recordings were mainly modified from Shao et al (2014). Fish were anesthetized with 0.025 % buffered MS-222 (ethyl 3-aminobenzoate, methanesulfonic acid salt), and then immobilized through an injection of gallamine triethiodide (Flaxedil; Sigma, St. Louis, MO, USA.…”
Section: Electroretinogram Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second scan was executed in the same region to confirm that the visual pigment was bleached. All data were analyzed by a statistical program to obtain the λ max of the photoreceptor [Loew, 1994], which is an approach that was successfully used in our previous work [Wang et al, 2008[Wang et al, , 2009[Wang et al, , 2011Chang et al, 2009Chang et al, , 2015Shao et al, 2014]. Briefly, the absorbance curve was first normalized and then transformed from wavelength to frequency [MacNichol, 1986].…”
mentioning
confidence: 99%
“…To remove variations between tests, values were normalized to a 0-100% scale, where 100% indicated the maximum sensitivity spectrum. This ERG method was applied in our earlier work on fish vision in the three-spined stickleback [Shao et al, 2014] and bitterlings . …”
mentioning
confidence: 99%